Individual Strivings in Social Comparison Processes: Achievement Motivation Goals in the Big-Fish-Little-Pond Effect - Cecalupo, Alessandra; Marini, Mara; Scarci, Federica; Livi, Stefano (Frontiers in Psychology, 2022)
In school settings, adolescents recur to different sources of information in order to create their beliefs about future possibilities. Social comparison processes and personal goals related to achievement surely play an important role in shaping these beliefs. Drawing upon literature concerning both the Big-Fish-Little-Pond effect – which focuses on how school mates’ achievements impact on students’ perceptions about their capabilities and present and future possibilities – and the Achievement Goal Theory, the present study aims to understand how adolescents attending the last year of secondary school (n = 689; Mage = 18.15; SD = 0.57) perceive their possibilities of potentially having a better future than their classmates. In particular, we seek to understand in which way this perception is influenced by the students’ relative perceived position in their class – which accounts for the social comparison process – and its interaction with different types of achievement orientations (mastery goals, performance-approach goals and performance-avoidance goals).